2014
DOI: 10.1021/pr500971h
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Separation by Capillary Electrophoresis Prior to Analysis by Top-Down Mass Spectrometry Enables Sensitive Characterization of Protein Complexes

Abstract: Intact protein analysis via top-down mass spectrometry (MS) provides a bird’s eye view over the protein complexes and complex protein mixtures with the unique capability of characterizing protein variants, splice isoforms, and combinatorial post-translational modifications (PTMs). Here we applied capillary electrophoresis (CE) through a sheathless CE–electrospray ionization interface coupled to an LTQ Velos Orbitrap Elite mass spectrometer to analyze the Dam1 complex from Saccharomyces cerevisiae. We achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…CZE and RPLC can provide orthogonal separation of intact proteins. It has been reported that CZE-MS approached better characterization of Dam1 complex subunits in terms of separation efficiency and resolution with 100-times less sample consumption compared to RPLC-MS. [11] In addition, CZE can separate protein(s)/protein complexes in native condition. [46,47] Very recently, Belov et al characterized a ribosomal isolate from E. coli using CZE-MS/MS in native condition, leading to the identification of 42 ribosomal proteins and 137 proteoforms in a single experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CZE and RPLC can provide orthogonal separation of intact proteins. It has been reported that CZE-MS approached better characterization of Dam1 complex subunits in terms of separation efficiency and resolution with 100-times less sample consumption compared to RPLC-MS. [11] In addition, CZE can separate protein(s)/protein complexes in native condition. [46,47] Very recently, Belov et al characterized a ribosomal isolate from E. coli using CZE-MS/MS in native condition, leading to the identification of 42 ribosomal proteins and 137 proteoforms in a single experiment.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Han et al employed the sheathless interface based CZE-MS/MS for top-down proteomics of a Pyrococcus furiosus lysate, resulting in identification of 291 proteoforms with RPLC fractionation and CZE-MS/MS. [10] Han et al also characterized the Dam1 protein complex using the sheathless interface based CZE-MS. Their results showed that CZE-MS approached complete characterization of the protein complex with 100-times less sample consumption compared to RPLC-MS. [11] Sensitive and comprehensive characterization of intact pharmaceutical proteins via the sheathless interface based CZE-MS has been demonstrated recently, thus leading to detection of over 250 different isoforms of recombinant human erythropoietin [12] and 138 proteoforms from recombinant human interferon-β1. [13] The sheathless interface based CZE-MS has also been applied for characterization of intact histones by the Lindner group.…”
Section: Introductionmentioning
confidence: 99%
“…In native MS, where physiological or near-physiological conditions are required, the task of separating non-denatured proteins and protein complexes at high resolution is further complicated. Conventional separation techniques compatible with native MS include size exclusion chromatography (SEC) [18], ion exchange chromatography (IEX) [19], hydrophobic interaction chromatography (HIC) [20], affinity chromatography [21], capillary isoelectric focusing (cIEF) [22, 23], native gel-eluted liquid fraction entrapment electrophoresis (GELFrEE) [24, 25], native polyacrylamide gel electrophoresis [26], capillary zone electrophoresis (CZE) [27, 28] and flow field-flow fractionation (F4) [29, 30]. However, for many of these methods, online interfacing to a mass spectrometer is challenging or yet impossible.…”
Section: Introductionmentioning
confidence: 99%
“…As with Bottom-Up methodologies, ionisation is most commonly performed by electrospray ionisation (ESI) coupled to reverse phase chromatography [159] or increasingly, capillary electrophoresis [153,157,160]. While other ionisation methods are available, ESI offers benefits that other methods do not.…”
Section: Top-down Mass Spectrometry Methods For Proteoform Quantitmentioning
confidence: 99%